Perbedaan Efikasi Diri Berdasarkan Tipe Pola Asuh Orangtua pada Remaja Tengah di Denpasar - Widiyanti, A.A. Mas Diah; Marheni, Adijanti (Jurnal Psikologi Udayana, 2013)
Parenting style are all forms of interaction process between parent and child that will give effect to the personality development of children. The growth of self-efficacy in adolescents is evolve regularly. Beginning of the growth of self-efficacy focused on the elderly, then influenced by siblings, peers, and other adults. In this case the parents and family members have an important role in the formation of adolescent self-efficacy. Patterns of parenting and good interaction with family members is a contributing factor to form a positive self-efficacy in adolescents. Different dynamics of parenting style will also form a different self efficacy in adolescents. The aim of this research is to investigate the difference of self-efficacy based on parenting style of middle adolescents in Denpasar. This research is quantitative comparison. The subjects were middle adolescents in Denpasar as many as 380 people to the criteria of Grade X and XI Senior High School in Denpasar. The sample were selected using Area Probability Random Sampling Method. Method of data collection using the Parenting Scale has tested its validity, the reliability of 0.952 as well as Self-Efficacy Scale also has reliability 0.962. Distribution of the data obtained indicates normal data and homogeneous. Statistical analysis methods with techniques of comparative One Way Anova. Results obtained F = 22.275, p = 0.000 and analysis of Post Hoc get results indicate that the authoritative parenting has a significance of 0.000 Authoritarian, authoritative parenting with 0,000 Permissive, Authoritarian parenting Permissive amounted to 0.163. It means that the difference in self-efficacy based on the type of authoritative parenting with authoritarian, self-efficacy differences with Permissive parenting authoritative, and there is no difference in self-efficacy on the Authoritarian Permissive parenting adolescents in the middle of Denpasar. Keywords : Parenting Style, Self-Efficacy, Middle Adolescents